Is increasing nodal count associated with improved recurrence‐free and overall survival following standard right hemicolectomy for colon cancer?. Issue 3 (7th May 2022) - Hayes, Ian P.; Milanzi, Elasma; Gibbs, Peter; Faragher, Ian; Reece, Jeanette C.
Abstract: Background and Objectives: Increasing lymph node harvest for right‐sided colon cancer is associated with improved overall survival (OS), but most relevant studies failed to report the extent of resection. We examined the association between increasing lymph node count with standard right hemicolectomy according to nodal status and prognostic outcomes in right‐sided tumors. Methods: Retrospective analysis of prospectively collected clinical data from patients with proximal colonic adenocarcinomas ( n = 1390) following right hemicolectomy. Associations between lymph node counts (0–12 vs. 13–15, 16–20, and >20) and recurrence‐free survival (RFS) and OS were examined using multivariate Cox modeling adjusted for confounders. Results: We found no association between increasing nodal count and RFS, regardless of nodal status. In the absence of nodal metastases, increasing nodal count (16–20 and >20 vs. 0–12 nodes) was associated with 57% (95% confidence interval [CI]: 0.21–0.89) and 52% (95% CI: 0.24–0.95) improved OS, respectively. In the presence of nodal metastases, increasing nodal count was not associated with OS. Adjuvant chemotherapy did not modify this effect. Conclusion: Increasing nodal count (>15 nodes) with right hemicolectomy was not associated with improved RFS. Improved OS was only found for node‐negative tumors, casting some doubt on the benefits of resecting more lymph nodes in the presence of nodal metastases.